GAMBARAN HISTOPATOLOGIS LAMBUNG TIKUS WISTAR (RATTUS NOVERGICUS) YANG DIBERIKAN ALKOHOL - Kololu, Dewi Febry; Lintong, Poppy M.; Loho, Lily (e-Biomedik, 2014)
Abstract: Alcohol has become aglobal problem. When it is consumed alcohol can disrupt the structure and function of the digestive tract. Objective: To reveal the histopathological features of the gastric of Wistar rats that are administered with bir, wine, whisky and cap tikus. Method: Experimental research using 15 rats that ware fasted and divided into 5 groups those are group control group which was treated by water, group A which was treated by beer (4.9% alcohol),group B which was treated by wine (14% alcohol), group C which was treated by whiskey (43% alcohol),and group D rats which wastreated by cap tikus(70% alcohol). The treatment of the test animals is done in 5 days. Results:In the control group on mucosa, submucosa, muscularis and serosa layers,inflammatory cells are also seen.In group Ainflammatory cells found on submucosal layer, intestinal metaplasia, and dilation of blood vessels. In group B inflammatory cell, intestinal metaplasia and dilation of blood vessels are found.In group C erosion, inflammatory cells, intestinal metaplasia and dilation of blood vessels are found.In group D submucosal necrosis, inflammatory cells, intestinal metaplasia and hyperemia are found. Conclusions: The provision of alcoholic drinks (beer, wine, whiskey, and cap tikus) in wistar can cause acute gastritis and of the high alcohol content (70% alcohol content)will be accompanied by gastric necrosis. Keywords: Beer, wine, whisky, cap tikus, gastritis.Â Â  Abstrak: Alkohol telah menjadi masalah global. Ketika dikonsumsi, alkohol dapat mengganggu struktur dan fungsi dari saluran pencernaan. Tujuan: Untuk mengetahui gambaran histopatologi lambung tikus wistar yang diberikan bir, minuman anggur, whisky, dan cap tikus. Metode: Penelitian eksperimental menggunakan 15 ekor wistar yang dipuasakan kemudian dibagi menjadi 5 kelompok yaitu kelompok kontrol diberi minum air, kelompok A diberi perlakuan bir (kadar alkohol 4,9%), kelompok B diberi perlakuan anggur (kadar alkohol 14%), kelompok C diberi perlakuan whisky (kadar alkohol 43%), kelompok D diberi perlakuan cap tikus (kadar alkohol 70%). Perlakuan hewan uji selama 5 hari. Hasil: Pada kelompok kontrol tampak lapisan mukosa, submukosa, muskularis dan serosa, terlihat juga sel radang. Pada kelompok A didapatkan sel radangpada lapisan submukosa, metaplasia intestinal, dan pelebaran pembuluh darah. Pada kelompok B didapatkan sel radang, metaplasia intestinal dan pelebaran pembuluh darah.Pada kelompok C didapatkan erosi, sel radang, dan metaplasia intestinal dan pelebaran pembuluh darah.Pada kelompok D didapatkan nekrosis pada submukosa, sel radang, metaplasia intestinal dan hiperemi. Simpulan: Pemberian minuman beralkohol (bir, anggur, whisky, dan cap tikus) pada wistar dapat menyebabkan gastritis akut dan pada kadar alkohol yang tinggi (kadar alkohol 70%) disertai dengan nekrosis lambung. Kata Kunci: Bir, anggur, whisky, cap tikus, gastritis.